Enhancing oxygen exchange kinetics of solid oxide fuel cell cathode: Unleashing the potential of higher order Ruddlesden-Popper phase surface modification - Saher S.; Tan C.Y.; Ramesh S.; Yap B.K.; Ong B.H.; Al-Furjan M.S.H. (Elsevier B.V., 2024)
Tailoring the electrode surface represents a promising strategy to enhance electrochemical performance while preserving base material integrity. Achieving appropriate surface coverage with catalytic active oxide material is critical for efficient oxygen transport at the triple phase boundary (TPB). To further explore this approach, the perovskite structure La0.6Sr0.4Co0.2Fe0.8O3-? (LSCF) is decorated with a higher order Ruddlesden-Popper phase Pr4Ni3O10+? (PNO). This combination is being investigated using electrical conductivity relaxation (ECR) technique to study the oxygen exchange kinetics. Samples with varying surface coverage of PNO are examined in a temperature range of 650 C850 C, with a step change in pO2 between 0.1 atm and 0.21 atm. The chemical diffusion coefficient, Dchem, remains invariant across all the samples, however, the surface exchange coefficient, kchem, varies with the surface coverage of PNO. Notably, the coated sample with a PNO loading content of 0.28 mg cm?2, referred to as PNO5, demonstrates a significant enhancement of nearly two orders of magnitude in kchem compared to bare LSCF at 650 C. This substantial improvement is ascribed to the increased active sites of ORR within the TPB region and the facilitated electron access through tunneling from LSCF to the coated phase. Pulse isotopic exchange (PIE) measurements on the fractionated powders confirm the fast surface exchange kinetics of PNO. Such remarkable oxygen exchange characteristics encourage the use of PNO, along with LSCF, as potential candidates for SOFC cathodes. 2023 Elsevier B.V.